2014
DOI: 10.1016/j.enpol.2013.07.038
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of electrochromic windows impact in the energy performance of buildings in Mediterranean climates

Abstract: Energy performance analysis of Electrochromic (EC) windows is carried out. EC glass and control strategies are modeled and implemented in ESP-r. EC windows are evaluated, on a test prototype, as an alternative to shading devices. Set-points and measured variables are used to control optical properties of EC glass. Within this context, the paper focuses on the energy savings that may occur when using electrochromic (EC) windows, an interesting emerging technology alternative to shading devices to control solar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(46 citation statements)
references
References 41 publications
(37 reference statements)
1
45
0
Order By: Relevance
“…In order to reduce solar heat gain and still retain a satisfactory level of daylighting energy-efficient designs on window configurations are needed [17]. Appropriate solar protection or glazings with controllable properties can assist significantly toward the enhancement of building energy performance especially during the cooling season and for eastern or western facades in particular [18].…”
Section: Discussionmentioning
confidence: 99%
“…In order to reduce solar heat gain and still retain a satisfactory level of daylighting energy-efficient designs on window configurations are needed [17]. Appropriate solar protection or glazings with controllable properties can assist significantly toward the enhancement of building energy performance especially during the cooling season and for eastern or western facades in particular [18].…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies of electrochromic glazings have found that the technology could save 10%e20% primary energy consumption in perimeter building zones in commercial buildings across much of the U.S. relative to stocktypical windows [3]. A recent simulation study found cooling energy savings as high as 37 kWh/m 2 of glass for east and west facing facades in a Mediterranean climate compared with single and double pane windows [4]. Another simulation study found dynamic glazings applied to a split-pane window produced lighting savings of 37%e48% compared with a static window with occupant controlled blinds [5].…”
Section: Introductionmentioning
confidence: 98%
“…The spectral modulation capabilities and reversible redox properties of EC materials have led to the applications of visualized-transducers [3], windows [4,5], switchable mirrors [6], displays [7,8], and energy-saving buildings [9,10]. As far as solar-attenuation smart windows are concerned, a variety of inorganic [11,12] and organic [13,14] materials have been investigated and processed as thin films for device assembly to date.…”
Section: Introductionmentioning
confidence: 99%